Challenges to Breastfeeding Initiation and Duration for Teen Mothers. Issue 3 (May 2017) - Cota-Robles, Sonia; Pedersen, Laura; LeCroy, Craig Winston
Abstract: Purpose: The purpose of this study was to evaluate breastfeeding practices of teen mothers in a pre- and postnatal education and support program. Study Design and Methods: We studied breastfeeding practices of primarily Hispanic and non-Hispanic White teen mothers who participated in the Teen Outreach Pregnancy Services (TOPS) program, which promoted breastfeeding through prenatal programming and postpartum support. Analyses identified the most common reasons participants had not breastfed and, for those who initiated breastfeeding, the most common reasons they stopped. Results: Participants ( g = 314) reported on whether and for how long they breastfed. Nearly all participants reported initiating breastfeeding but few breastfed to 6 months. For the most part, reasons they reported stopping breastfeeding paralleled those previously reported for adult mothers across the first several months of motherhood. Clinical Implications: We found that teen mothers can initiate breastfeeding at high rates. Results highlight areas in which teen mothers' knowledge and skills can be supported to promote breastfeeding duration, including pain management and better recognizing infant cues. Our findings expand limited previous research investigating reasons that teen mothers who initiate breastfeeding stop before 6 months. Abstract : Breastfeeding practices of teen participants in a community outreach program that promoted breastfeeding through prenatal and postpartum support were studied. Nearly all teens reported initiating breastfeeding but few breastfed to six months. Teens stopped breastfeeding for the same reasons reported by adult mothers. Findings highlight areas in which teen mothers' knowledge and skills can be supported to promote breastfeeding duration, including pain management and better recognition of infant cues.